Entamoeba histolytica phagocytosis of human erythrocytes involves PATMK, a member of the transmembrane kinase family. - Douglas R Boettner (Public Library of Science (PLoS), 2008)
Entamoeba histolytica is the cause of amebic colitis and liver abscess. This parasite induces apoptosis in host cells and utilizes exposed ligands such as phosphatidylserine to ingest the apoptotic corpses and invade deeper into host tissue. The purpose of this work was to identify amebic proteins involved in the recognition and ingestion of dead cells. A member of the transmembrane kinase family, phagosome-associated TMK96 (PATMK), was identified in a proteomic screen for early phagosomal proteins. Anti-peptide affinity-purified antibody produced against PATMK demonstrated that it was a type I integral membrane protein that was expressed on the trophozoite surface, and that co-localized with human erythrocytes at the site of contact. The role of PATMK in erythrophagocytosis in vitro was demonstrated by: (i) incubation of ameba with anti-PATMK antibodies; (ii) PATMK mRNA knock-down using a novel shRNA expression system; and (iii) expression of a carboxy-truncation of PATMK (PATMK(delta932)). Expression of the carboxy-truncation of PATMK(delta932) also caused a specific reduction in the ability of E. histolytica to establish infection in the intestinal model of amebiasis, however these amebae retained the ability to cause hepatic abscesses when directly injected in the liver. In conclusion, PATMK was identified as a member of the TMK family that participates in erythrophagocytosis and is uniquely required for intestinal infection.